KEY ROLES OF FEMALE ULAMA IN DEVELOPING MULTICULTURAL ISLAMIC EDUCATION IN MANADO, INDONESIA - Arhanuddin Salim; Adri Lundeto; Muh Idris; Amiruddin Amiruddin; Rahman Mantu (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2026)
This study aimed to examine the key roles of female ulama in developing multicultural Islamic education in Manado City, North Sulawesi, Indonesia, where Muslims live as a religious minority within a Christian-majority society. This research employed a qualitative case study approach to explore the educational practices of female religious leaders in community settings. Data were collected through in-depth interviews with fifteen female ulama, participant observation of religious learning activities, and document analysis of teaching materials and digital da‘wah content. The findings indicated that female ulama played significant roles as community-based Islamic educators who construct persuasive and contextual religious authority within non-formal educational spaces. Their educational activities were conducted through Qur’anic study circles, women’s religious gatherings (majelis taklim), family and parenting education, digital religious teaching, and participation in community interaction. These practices promote values of religious moderation, tolerance, civic responsibility, and social harmony in a multicultural environment. The study also showed that female ulama actively responded to conservative and exclusive religious narratives by providing contextual explanations and encouraging reflective understanding of Islamic teachings. The findings implied that female religious educators played an important role in strengthening inclusive Islamic education and promoting social harmony in minority Muslim contexts.